2014
DOI: 10.5152/balkanmedj.2014.13267
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Cost Analysis of Cell Saver Auto Transfusion System in Total Knee Arthroplasty

Abstract: Blood loss and replacement during surgery is a controversial issue in major orthopaedic surgery such as Total Knee Arthroplasty (TKA). Allogeneic blood transfusion causes legal problems and concerns in terms of transmission of transfusion-related diseases. Therefore, cell saver systems (CSS) were developed to minimize the need for allogeneic blood transfusion. However, contradictory results have arisen from studies examining the use of CSS to reduce the need for allogeneic blood transfusion in primary TKA (1-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Allogenic blood transfusion may be related to systemic complications such as anaphylactic reaction, immunological rejection, hemolytic reaction, infectious disease, and metabolic disorders prolonging the duration of hospitalization and causing serious social economic burden [ 5 ]. So it is crucial to minimize the bleeding and transfusion requirements for the patients undergoing TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Allogenic blood transfusion may be related to systemic complications such as anaphylactic reaction, immunological rejection, hemolytic reaction, infectious disease, and metabolic disorders prolonging the duration of hospitalization and causing serious social economic burden [ 5 ]. So it is crucial to minimize the bleeding and transfusion requirements for the patients undergoing TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [4] reported that in the THA procedure, the blood loss ranged between 1000 and 2000 ml, and this increased the requirement of allogeneic blood transfusion. However, allogeneic blood transfusion might increase the risk of adverse effects, such as viral infection, immune response, cardiovascular dysfunction, added cost and even death [7][8][9][10][11][12][13]. Recently, the enhanced recovery after surgery protocol has been improved in THA, and the key to the improvement is the blood management [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 4 ] Allogenic blood transfusion is associated with adverse events, such as hemolytic reactions, immunologic reactions, disease transmission, transfusion-related acute renal failure, and cardiovascular dysfunction, resulting in financial burdens and potentially life-threatening effects on patients. [ 5 7 ] To date, various strategies have been attempted to minimize blood loss, including drug intervention, autologous donation, and allogenic blood transfusion. [ 8 ] In addition, several methods for bleeding control have been successfully employed in an effort to reduce postoperative blood loss and transfusion, including drain-clamping, tranexamic acid (TXA) administration, and tourniquets, among others.…”
Section: Introductionmentioning
confidence: 99%